Zn-promoted FeSx/γ-Al2O3 catalyst for stable selective reduction of high-concentration SO2 with methane: synergistic mitigation of carbon and sulfur deposition - Songlin Qu; Tingting Ge; Zhonghao Zhang; Yuxia Li; Yuchao Li; Ming Wang; Haofei Huang; Cuncun Zuo (Fuel, 2026)

Therapeutic effects of 1,25-dihydroxyvitamin D3 with astragalus polysaccharide on insulin resistance in gestational diabetes mellitus rat models - Shuqi Yan; Haoyan Ma; Wenjian Li; Jiayuan Qu; Ming Wei; Chong Tan; Qizheng Pan; Shuping Ren; Yuhong Wang (Molecular Biology Reports, 2026)

Computational study on the hydrothermal cracking routes of N-cyclohexylnaphthalen-1-amine based on density functional theory - Shao-Xuan Zhong; Wei Li; Jia-Wei Qu; Ming-Lan Ge; Yuan-Liang Yang; Jian-Qiang Tao; Jing Wang (Fuel, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Multi-scale mechanistic and life cycle assessment of polydopamine-functionalized hydrochar for sustainable Cu2 + capture - Leicheng Lv; Nan Li; Zhuangzhuang Qu; Hai Liang; Ming Yang (Process Safety and Environmental Protection, 2026)

OsSultr1;1 and OsZIP4 mediate cadmium uptake and transport in rice: evidence from high and low Cd-accumulators - Xin Qu; Chen He; Bingcai Xiong; Changfu Wu; Haoran Li; Xiaoyan Song; Shufeng Wang; Hongxia Du; Ming Ma (Journal of Hazardous Materials, 2026)

Key exposure components and oxidative stress-driven health risks assessment of oil mist generated by metalworking fluids in industrial building environment - Yang Yang; Yilin Li; Yuming Zhang; Yi Wang; Yalin Liu; Ming Liu; Xudong Li; Yifan Qu; Mengdan Qiao; Qingfeng Cao (Journal of Hazardous Materials, 2026)

Axial compression failure characteristics of composite armour layers in unbonded flexible risers - Qingsheng Liu; Lei Ding; Zhongyuan Qu; Jiawei He; Gang Wang; Qianqian Sui; Ming Li (Ocean Engineering, 2026)

A dynamic wave age method and simplified model for wind-sea and swell identification - Xiaojun Qu; Hao Li; Ming Li (Ocean Engineering, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Supramolecular binder ensures iodine stability in four-electron conversion zinc-iodine batteries - Wentao Qu; Pengchao Li; Zhongwen Zhang; Yali Xu; Constantinos Soutis; Liwei Mi; Ming Zhang (Chemical Engineering Journal, 2026)

Influence Mechanism of Complex Natural Fractures on Fracture Propagation of Multi-well Fracturing in Laminated Shale Reservoirs: A Numerical Study - Tiankui Guo; Bo Zhang; Ming Chen; Yanlong Li; Yongzan Liu; Fengshou Zhang; Nengyou Wu; Zhanqing Qu (Rock Mechanics and Rock Engineering, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Spatial distribution, contamination characteristics and health hazard potential of soil potentially toxic elements under different reclamation modes in coal mining subsidence areas - Min Tan; Xuanxuan Li; Ruoyun Nian; Xiyuan Song; Jihong Dong; Junfeng Qu; Ming Hao (Environmental Monitoring and Assessment, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

A hyper-crosslinked ionic polymer catalyzing CO2 one-pot two-step to dimethyl carbonate via HCO3-/OH- synergy - Jingya Yang; Ming Sun; Qinghua Qu; Jiquan Liang; Cheng Fang; Lei Wang; Hongping Li; Jing Ding; Hui Wan; Guofeng Guan (Journal of Environmental Chemical Engineering, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Radial oxygen loss of Typha latifolia outperforms microbial effects in heavy metal(loid) stabilization - Taicong Liu; Liying Lan; Yuanyuan Li; Daijie Chen; Ming Ao; Shuting Tang; Haojie Qu; Chao Jin; Miaoyue Zhang; Roland Bol; Jean Louis Morel; Zhihong Xu; et al. (Environmental Research, 2025)

Cost-effective n-type liquid flow thermocells with giant ionic thermopower and power density through solvation entropy engineering for low-grade heat harvesting - Zhuo Liu; Zhongyi Li; Ming Qu; Huidong Yang; Junxiang Tang; Fanghao Zhong; Xiang Wei; Yangfan Song; Zhenfei Liu; Hongwei Chen (Chemical Engineering Journal, 2025)

Temperature-driven deterministic assembly processes facilitate the coexistence of photoautotrophic communities in greenfield biocrusts across China - Chao Chang; Li Gao; Arash Zamyadi; Siwan Liu; Ning Qu; Ming Li (Plant and Soil, 2025)

Inverse design of three-dimensional electrocatalytic oxidation process for water purification via machine learning and DFT-based descriptors - Linjin Li; Qiyao Wang; Yaoze Wang; Guangfei Qu; Yingying Cai; Rui Xu; Ming Jiang; Nanqi Ren (Process Safety and Environmental Protection, 2025)

Small-molecule fluorescent probes for imaging intracellular amyloid toxicity induces ferroptosis via HClO fluctuation in Alzheimer's disease - Wenhui Ma; Bingbing Tang; Han Zhang; Yixin Qu; Jinfeng Luan; Kelong Wang; Wenbo Chen; Xijuan Wang; Xinran Liu; Hongyan Zhao; Haixia Li; Ming Luo; et al. (Analytica Chimica Acta, 2025)

Polarized microenvironment-modulated covalent organic frameworks with nickel single atoms for enhanced CO2 photoreduction - Piyan Wang; Yingchen Dai; Zisheng Song; Yan Wang; Jingru Wei; Zhijie Liu; Yuting Ma; Fengyi Yang; Jiafu Qu; Shuzhi Liu; Yahui Cai; Xiaogang Yang; et al. (Chemical Engineering Journal, 2025)

Melatonin enhances salt tolerance by promoting CcCAD10-mediated lignin biosynthesis in pigeon pea - Feng Pan; Hongquan Li; Ming Qu; Xiaoli An; Jie Yang; Yujie Fu (Theoretical and Applied Genetics, 2025)

Emission factors and driving forces of provincial-level CO2 from electricity production and consumption in China from 2013 to 2020 - Ruoxi Xiong; Chenling Fu; Huimin Chang; Nan Li; Shen Qu; Dong Zhao; Changqing Xu; Jianchuan Qi; Ming Xu (Journal of Environmental Management, 2025)

Two-stage anomaly detection for imbalanced bridge data by attention mechanism optimisation and small sample augmentation - Chun-Xu Qu; Yun-Tao Yang; Hong-Ming Zhang; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Heteronuclear interactions of Pd-M (M = Ni, Cu, Fe, In) bimetallic on hollow dodecahedron nickel cobalt oxide for enhanced low-temperature CO2 hydrogenation to formate - Songqi Li; Kai Zhang; Jundie Hu; Bailing Zhong; Xiaogang Yang; Yahui Cai; Chang Ming Li; Qiming Sun; Jiafu Qu (Chemical Engineering Journal, 2025)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Anomaly detection of massive bridge monitoring data through multiple transfer learning with adaptively setting hyperparameters - Chun-Xu Qu; Hong-Ming Zhang; Ting-Hua Yi; Zhi-Yuan Pang; Hong-Nan Li (Engineering Structures, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Establishing carbon footprints for modular integrated construction logistics using cyber-physical internet routers - Chung-lam Ng; Ming Li; Ray Y. Zhong; Xinye Qu; George Q. Huang (Transportation Research Part D: Transport and Environment, 2024)

Effects of particle size of CL-20 on its thermal decomposition and combustion characteristics - Hexin Liu; Fengqi Zhao; Xiao Xie; Yifan Jiang; Zhoufeng Jiang; Renhui Ruan; Ming Zhang; Hui Li; Wengang Qu (Fuel, 2024)

Green tea polyphenols reduced Porphyromonas gingivalis virulence and ameliorated aggravated gut inflammation by improving immunity and gut microbiota dysbiosis - Ming Li; Ru Qu; Ping Li; Xuan Mo; Juan Liu; Zhenjiang Zech Xu (Food Bioscience, 2024)

Performance evaluation of underground thermal storage integrated dual-source heat pump systems - Liang Shi; Ming Qu; Xiaobing Liu; Tomas Pablo Venegas; Lingshi Wang; Jin Dong; Borui Cui; Haowen Xu; Xiaoli Liu; Yanfei Li (Energy and Buildings, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Research on fracture propagation of hydraulic fracturing in a fractured shale reservoir using a novel CDEM-based coupled HM model - Bo Zhang; Tiankui Guo; Ming Chen; Jiwei Wang; Zhanqing Qu; Haiyang Wang; Heng Zheng; Wuguang Li (Computers and Geotechnics, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

Accurate genomic selection using low-density SNP panels preselected by maximum likelihood estimation - Shiyu Qu; Sheng Lu; Yang Liu; Ming Li; Songlin Chen (Aquaculture, 2024)

Effects of dissolved organic matter, pH and nutrient on ciprofloxacin bioaccumulation and toxicity in duckweed - Mengnan Shen; Yi Hu; Ke Zhao; Zhi Qu; Chen Lyu; Binshuo Liu; Ming Li; Xiaodan Bu; Chenyang Li; Shuang Zhong; Jie Cheng (Aquatic Toxicology, 2024)

Assessment of the seismic hazard in North China by combining micro-seismicity records and geodetic observations - Yuan Gao; Wei Qu; Qin Zhang; Jiuyuan Li; Da Li; Yuhao Wang; Ming Hao (Tectonophysics, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Characteristics and Geological Significance of High-precision Aeromagnetic Data in LinFen-YunCheng - Ming Wang; Jin-hong Qu; Xiao-xing Lin; Zhen-jun Liu; Fang Li (Applied Geophysics, 2023)

Dissolved inorganic carbon budget of two alpine catchments in the central Tibetan Plateau: Glaciation matters - Zhengliang Yu; Jianhong Li; Guangjian Wu; Dongmei Qu; Fei Wang; Xiaoxing Ming; Haiying Qiu; Zhu Liu; Philipp Maurischat (Science of The Total Environment, 2023)

Molten salt-assisted anti-defect engineering to tailor ordered, highly crystalline g-C3N4 nanorods for efficient photocatalytic H2O2 production - Tingyu Yang; Yanqi Tang; Fengyi Yang; Jiafu Qu; Xiaogang Yang; Yahui Cai; Feng Du; Chang Ming Li; Jundie Hu (Chemical Engineering Journal, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

One-stage partial nitrification/anammox system with short sludge retention time and low mixed liquor suspended solids long-term control: Establishment, performance and sludge characteristics - Cong Wang; Li-Fang Liu; Shu-Jun Zhang; Zhi-Ming Qu; Wei-Kang Qi; Yong-Zhen Peng (Science of The Total Environment, 2023)

Synergistic effects of pyrolysis temperature, iron ion concentration and solid/liquid ratio on the properties and Cr(VI) removal performance of magnetic carbon - Qiang Qu; Ling Qiu; Ming-Zhuo Li; Guo-Tao Sun; He-Yu Chen; Xiao-Hui Guo (Journal of Water Process Engineering, 2023)

Charge polarization-modulated Pd-Ni(OH)2 hybrids in mesoporous silica SBA-15 for efficient low-temperature CO2 hydrogenation to formate - Jiafu Qu; Songqi Li; Zhiyuan Deng; Jundie Hu; Xiaogang Yang; Yahui Cai; Feng Du; Bailing Zhong; Chang Ming Li; Qiming Sun (Chemical Engineering Journal, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Bifunctional honeycomb hierarchical structured 3D/3D ReS2/ZnIn2S4-Sv heterojunction for efficient photocatalytic H2-evolution integrated with biomass oxidation - Jundie Hu; Xue Li; Jiafu Qu; Xiaogang Yang; Yahui Cai; Tingyu Yang; Fengyi Yang; Chang Ming Li (Chemical Engineering Journal, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Investigating the effects of local weather, streamflow lag, and global climate information on 1-month-ahead streamflow forecasting by using XGBoost and SHAP: two case studies involving the contiguous USA - Jin Liu; Kun Ren; Tingzhen Ming; Jihong Qu; Wenxian Guo; Haohao Li (Acta Geophysica, 2022)

Palmitoylation of MDH2 by ZDHHC18 activates mitochondrial respiration and accelerates ovarian cancer growth - Xuan Pei; Kai-Yue Li; Yuan Shen; Jin-Tao Li; Ming-Zhu Lei; Cai-Yun Fang; Hao-Jie Lu; Hui-Juan Yang; Wenyu Wen; Miao Yin; Jia Qu; Qun-Ying Lei (Science China Life Sciences, 2022)

Chloride-binding capacity of mortars composed of marine sand subjected to external chloride penetration - Congtao Sun; Ming Sun; Tao Tao; Feng Qu; Gongxun Wang; Peng Zhang; Yantao Li; Jizhou Duan (Journal of Oceanology and Limnology, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

The combined toxicity of binary mixtures of antibiotics against the cyanobacterium Microcystis is dose-dependent: insight from a theoretical nonlinear combined toxicity assessment method - Yeyong Wang; Cheng Gao; Zhi Qu; Ming Li (Environmental Science and Pollution Research, 2022)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Dynamic mechanical behavior and damage constitutive model of shales with different bedding under compressive impact loading - Xueru Fan; Ning Luo; Yishuo Yuan; Hanliang Liang; Cheng Zhai; Zhe Qu; Ming Li (Arabian Journal of Geosciences, 2021)

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Performances of six eupelmid egg parasitoids from China on Japanese giant silkworm Caligula japonica with different host age regimes - Yong-Ming Chen; Xing-Ran Qu; Tian-Hao Li; Asim Iqbal; Xingeng Wang; Zhi-Yong Ren; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2021)

Surface Temperature Changes Projected by FGOALS Models under Low Warming Scenarios in CMIP5 and CMIP6 - Shang-Min Long; Kai-Ming Hu; Gen Li; Gang Huang; Xia Qu (Advances in Atmospheric Sciences, 2021)

Present-Day Crustal Deformation Within the Western Qinling Mountains and Its Kinematic Implications - Ming Hao; Yuhang Li; Qingliang Wang; Wenquan Zhuang; Wei Qu (Surveys in Geophysics, 2021)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Elastic reverse-time migration in irregular tunnel environment based on polar coordinates - Ying-Ming Qu; Chang Zhou; Qurmet Worral; Zhen-Chun Li; Chang-Bo Wang; Jun-Zhi Sun (Applied Geophysics, 2020)

Effects of topography on dynamic responses of single piles under vertical cyclic loading - Li-ming Qu; Xuan-ming Ding; Chong-rong Wu; Yong-hong Long; Jin-chuan Yang (Journal of Mountain Science, 2020)

Multiple attenuation using λ-f domain high-order and high-resolution Radon transform based on SL0 norm - Wen-Zhi Sun; Zhen-Chun Li; Ying-Ming Qu; Zhi-Na Li (Applied Geophysics, 2019)

Spontaneous mutations in FgSAD1 suppress the growth defect of the Fgprp4 mutant by affecting tri‐snRNP stability and its docking in Fusarium graminearum - Xiaoping Li; Zhili Fan; Ming Yan; Jia Qu; Jin‐Rong Xu; Qiaojun Jin (Environmental Microbiology, 2019)
Summary FgPrp4, the only kinase in the spliceosome, is not essential for viability, but is important for splicing efficiency in Fusarium graminearum . The Fgprp4 deletion mutant had severe growth defects but often produced spontaneous suppressors with faster growth rate. To better understand the suppression mechanism, we identified and characterized spontaneous mutations in the tri‐snRNP‐specific protein, FgSad1, which suppressed the growth defects of Fgprp4 . The L512P mutation was verified for its suppressive effects on Fgprp4 , suggesting that mutations in FgSad1 may have effects involving FgPrp4 phosphorylation on FgSad1. Phosphoproteomics analysis showed that FgSad1 may not be the direct substrate of FgPrp4 kinase. Furthermore, truncation analysis showed that the N‐terminal, extra RS‐rich region of FgSad1 is critical for its function and is post‐translationally modified. The P258S or S269P mutations in FgSad1 increased its interactions with the U5 protein FgPrp8 and the U4/U6 protein FgPrp31, which may result in tri‐snRNP stabilization. Additionally, the D76N mutation increased the association of FgSad1 with the U2 snRNP. These data indicate that suppressor mutations in FgSad1 increase the stability of the tri‐snRNP and/or the affinity of FgSad1 with U2 snRNP and therefore potentially facilitate the docking of tri‐snRNP into the spliceosome.

Multiparameter least-squares reverse time migration for acoustic—elastic coupling media based on ocean bottom cable data - Ying-Ming Qu; Chong-Peng Huang; Chang Liu; Chang Zhou; Zhen-Chun Li; Qurmet Worral (Applied Geophysics, 2019)

Comparison of monoculture and mixed culture (Scenedesmus obliquus and wild algae) for C, N, and P removal and lipid production - Zhi Qu; Pengfei Duan; Xubing Cao; Manli Liu; Li Lin; Ming Li (Environmental Science and Pollution Research, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

Effects of body mass index on the outcomes of in vitro fertilization in Chinese patients with polycystic ovary syndrome: a retrospective cohort study - Xiao-ming Pan; Zhong Lin; Nan Li; Jia-qi Wu; Dan-qing Chen; Yi-min Zhu; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2018)

Effects of nitrogen forms and supply modes on colony formation in Microcystis aeruginosa - Zhi Qu; Miaomiao Zhao; Pengfei Duan; Ming Li (Journal of Applied Phycology, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Cloning and Stress-Induced Expression Analysis of Calmodulin in the Antarctic Alga Chlamydomonas sp. ICE-L - Ying-ying He; Yi-bin Wang; Zhou Zheng; Fang-ming Liu; Mei-ling An; Xiao-dong He; Chang-feng Qu; Lu-lu Li; Jin-lai Miao (Current Microbiology, 2017)

Entire Frequency Domain Analysis of Rodent EEG and EMG Recordings Using Relative Thresholds - Ming-Ming Yan; Wei-Min Qu; Xin-Hong Xu; Zhi-Li Huang; Ming-Hui Yao (Sleep and Vigilance, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Changes and relations of photosynthesis and iron cycling in anoxic paddy soil amended with high concentrations of sulfate - Qin Chen; Rong Jia; Dong Qu; Ming Li (Environmental Science and Pollution Research, 2017)

Plant Volatiles Increase Sex Pheromone Attraction of Holotrichia parallela (Coleoptera: Scarabaeoidea) - Qian Ju; Xiao-qiang Guo; Xiao Li; Xiao-jing Jiang; Xiang-guo Jiang; Wan-li Ni; Ming-jing Qu (Journal of Chemical Ecology, 2017)

NFAT5 protects astrocytes against oxygen–glucose–serum deprivation/restoration damage via the SIRT1/Nrf2 pathway - Xun Xia; Bo Qu; Yun-Ming Li; Li-Bin Yang; Ke-Xia Fan; Hui Zheng; Hai-Dong Huang; Jian-Wen Gu; Yong-Qin Kuang; Yuan Ma (Journal of Molecular Neuroscience, 2017)

Prismatic and full-waveform joint inversion - Ying-Ming Qu; Zhen-Chun Li; Jian-Ping Huang; Jin-Li Li (Applied Geophysics, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Effects of semi-lunar tidal cycling on soil CO2 and CH4 emissions: a case study in the Yangtze River estuary, China - Nai-Shun Bu; Jun-Feng Qu; Hua Zhao; Qing-Wu Yan; Bin Zhao; Jing-Lan Fan; Chang-Ming Fang; Gang Li (Wetlands Ecology and Management, 2015)

Chemical constituents from Piper wallichii - Yan-Ni Shi; Lian Yang; Jin-Hua Zhao; Yi-Ming Shi; Yan Qu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Xing-Cong Li; Min Xu; Ying-Jun Zhang (Natural Product Research, 2015)

Structural control on pore-fracture characteristics of coals from Xinjing coal mine, northeastern Qinshui basin, China - Jiegang Liu; Bo Jiang; Ming Li; Zhenghui Qu; Linlin Wang; Lei Li (Arabian Journal of Geosciences, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Identification and genetic characterization of avian-origin H3N2 canine influenza viruses isolated from the Liaoning province of China in 2012 - Xinyan Yang; Chunguo Liu; Fei Liu; Dafei Liu; Yan Chen; Haifeng Zhang; Liandong Qu; Yijing Li; Donghua Xia; Ming Liu (Virus Genes, 2014)

Melt and fluid inclusion evidence for a genetic relationship between magmatism in the Shuangliao volcanic field and inorganic CO 2 gas reservoirs in the southern Songliao Basin, China - Zhichao Yu; Li Liu; Xiyu Qu; Shuang Zhao; Bing Zhou; Xiaoran Ming (International Geology Review, 2014)

Sirt1 Promotes Axonogenesis by Deacetylation of Akt and Inactivation of GSK3 - Xiao-hong Li; Chong Chen; Yue Tu; Hong-tao Sun; Ming-liang Zhao; Shi-xiang Cheng; Yang Qu; Sai Zhang (Molecular Neurobiology, 2013)

Antioxidant response and histopathological changes in brain tissue of pigeon exposed to avermectin - Ming Li; Tian-Zi You; Wen-Jun Zhu; Jian-Ping Qu; Ci Liu; Bing Zhao; Shi-Wen Xu; Shu Li (Ecotoxicology, 2013)

Effect of Random Inclusion of Wheat Straw Fibers on Shear Strength Characteristics of Shanghai Cohesive Soil - Jili Qu; Chencai Li; Baoshi Liu; Xinxing Chen; Ming Li; Zhaowei Yao (Geotechnical and Geological Engineering, 2013)

Role of NOD2 in regulating the immune response to Aspergillus fumigatus - Zhuo-zhe Li; Li-li Tao; Jing Zhang; Hui-jun Zhang; Jie-Ming Qu (Inflammation Research, 2012)

A meta-analysis of β1-adrenergic receptor gene polymorphisms in idiopathic dilated cardiomyopathy - Bo Jin; Qu-Zhen Ge-Shang; Yong Li; Wei Shen; Hai-Ming Shi; Huan-Chun Ni (Molecular Biology Reports, 2012)

Microstructures and Photocatalytic Properties of Fe3+/Ce3+ Codoped Nanocrystalline TiO2 Films - Yan-zhen Qu; Ming-ming Yao; Fang Li; Xiao-hu Sun (Water, Air, & Soil Pollution, 2011)

Varied association of prothrombin G20210A polymorphism with coronary artery disease susceptibility in different ethnic groups: evidence from 15,041 cases and 21,507 controls - Bo Jin; Yong Li; Qu-Zhen Ge-Shang; Huan-Chun Ni; Hai-Ming Shi; Wei Shen (Molecular Biology Reports, 2011)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

Recovery of transgenic orchid plants with hygromycin selection by particle bombardment to protocorms - Zhihua Yu; Minyong Chen; Lin Nie; Huafei Lu; Xiaotian Ming; Honghong Zheng; Li-Jia Qu; Zhangliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)